Comprehensive analysis of prostate cancer life expectancy, loss of life expectancy, and healthcare expenditures: Taiwan national cohort study spanning 2008 to 2019 - Liu, Pin-Chun; Lin, Yi-Sheng; Ou, Yen-Chuan; Hsu, Chao-Yu; Tung, Min-Che; Chiu, Ying-Ming (PLOS ONE, 2025)
Prostate cancer (PCa) is the second most commonly diagnosed cancer worldwide and the 5th leading cause of death from cancer for men in Taiwan. The incidence of synchronous metastatic PCa in Taiwan is higher than U.S. and Europe. We aim to present the latest life expectancy (LE), loss of LE, and lifetime cost associated with PCa in Taiwan. The PCa data are based on Taiwan Cancer Registry and National Health Insurance Database. Total 30,207 new cases of PCa were recorded during 2008-2019 nationwide. LE, estimated loss of LE and lifetime cost were stratified by age, cancer stage, Gleason score, grade group and serum PSA level at diagnosis. We compared LE and healthcare cost outcomes between synchronous metastatic PCa patients in 3 age groups. Among the 30,207 new cases, the low to intermediate risk groups, high-risk groups, and regional and metastatic PCa accounted for 54.1%, 13.2%, and 32.6% of cases, respectively. A considerable proportion of synchronous metastatic PCa was noted in Taiwan when compared with the U.S. For synchronous metastatic PCa, the highest LE is 9.22 years for ages 20-64 years, followed by ages 65-74 (8.29 years) and ages 75-89 years (4.58 years). The loss of LE in the three age groups is 13.63, 6.75, and 3.87 years, respectively. The healthcare cost of synchronous metastatic PCa in all age groups is higher than the average cost for PCa patients in Taiwan. This study provides real-world evidence to support health care policy-making and clinical decisions regarding PCa. Due to the high proportion of synchronous metastatic PCa in Taiwan, the findings of this analysis emphasize the importance of early detection of PCa, which can save LE and decrease the total cost burden on the healthcare system.